Reexamining the Link Between Economic Downturns and Racial Antipathy: Evidence That Prejudice Against Blacks Rises During Recessions. (October 2018) - Bianchi, Emily C.; Hall, Erika V.; Lee, Sarah
Scholars have long argued that economic downturns intensify racial discord. However, empirical support for this relationship has been mixed, with most recent studies finding no evidence that downturns provoke greater racial animosity. Yet most past research has focused on hate crimes, a particularly violent and relatively infrequent manifestation of racial antipathy. In this article, we reexamine the relationship between economic downturns and racial acrimony using more subtle indicators of racial animosity. We found that during economic downturns, Whites felt less warmly about Blacks (Studies 1 and 2), held more negative explicit and implicit attitudes about Blacks, were more likely to condone the use of stereotypes, and were more willing to regard inequality between groups as natural and acceptable (Study 2). Moreover, during downturns, Black musicians (Study 3) and Black politicians (Study 4) were less likely to secure a musical hit or win a congressional election.